2018
DOI: 10.15698/mic2018.10.650
|View full text |Cite
|
Sign up to set email alerts
|

A Cinderella story: how the vacuolar proteases Pep4 and Prb1 do more than cleaning up the cell’s mass degradation processes

Abstract: Recently, several research groups have assigned non-vacuolar functions to the well-known Saccharomyces cerevisiae vacuolar proteases Pep4 and Prb1, which are also known as proteinases A and B. These non-vacuolar activities seem to be autophagy-independent and stress-induced and suggest an unexplored but possibly prominent role for the proteases outside the vacuole. The functions range from the involvement in programmed cell death, to protection from hazardous protein forms and regulation of gene expression. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…In addition, Spt8, a subunit of the Spt-Ada-Gcn5 acetyltransferase (SAGA) complex and a calcineurin substrate, was required for Ca 2+ -mediated cytoprotection. Interestingly, the SAGA subunit Spt7 has been shown to be cleaved by Pep4, which results in the loss of Spt8 from the SAGA complex and the formation of a SAGA-like (SLIK) complex [ 62 , 63 ]. Altogether, these data clearly point to a crucial role of vacuolar function in Ca 2+ -mediated mitigation of αSyn proteotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Spt8, a subunit of the Spt-Ada-Gcn5 acetyltransferase (SAGA) complex and a calcineurin substrate, was required for Ca 2+ -mediated cytoprotection. Interestingly, the SAGA subunit Spt7 has been shown to be cleaved by Pep4, which results in the loss of Spt8 from the SAGA complex and the formation of a SAGA-like (SLIK) complex [ 62 , 63 ]. Altogether, these data clearly point to a crucial role of vacuolar function in Ca 2+ -mediated mitigation of αSyn proteotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that tre123244 has a high identity with the vacuole protease RB1 (NCBI YEL060C). PRB1 is shown to be involved in the proteolytic processing of the precursor proteins (Ogrydziak, 1993; Kerstens and Dijck, 2018). Therefore, it could be supposed that tre123244 is a vacuole protease and plays a key role in the basic cell metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…In filamentous fungi, many studies have demonstrated the importance of autophagy for differentiation, adaptation, development, and reproduction [ 75 , 76 , 77 , 78 ]. In addition, there is a relationship between autophagy-related stress responses and aspartic protease activity [ 79 , 80 ]. In the present work, we evidenced the role of aspartic protease inhibitors during the transition from mycelium to yeast in P. brasiliensis .…”
Section: Discussionmentioning
confidence: 99%